Probabilistic approach for failure assessment of steel structures in fire by means of plastic limit analysis - Nigro, E.; Bilotta, A.; Asprone, D.; Jalayer, F.; Prota, A.; Manfredi, G. (Fire safety journal, 2014)
The issue of fire scenarios approach to fire protection is often subject of ongoing discussions within the fire safety engineering community. The choice of an adequate number and type of fire scenarios is not always univocal and straightforward. The fire scenarios to be used in structural assessment are quite complicated to obtain. Their definition often involves significant large-scale fire tests and sophisticated numerical simulations, taking into account numerous factors. For this reason, it seems appropriate to introduce probabilistic tools to assess the most probable fire scenarios. This work proposes a probabilistic approach integrating the Monte Carlo simulation with plastic limit analysis in order to assess the probability of failure of a structure subjected to fire. The underlying assumptions related to spatial–temporal evolution of the fire action and the response of materials and structural members comply with Eurocode provisions. The procedure, mainly devoted to identify the most critical fire scenarios for the structural response, is illustrated by means of a case study represented by a steel braced structure, used as parking. Beyond the limitations related to the simplified assumptions, the outcomes of the analyses demonstrate the potential of the approach for choosing fire scenarios by means of a probabilistic procedure and for evaluating the probability of fire-induced progressive collapse. •The paper is aimed at evaluating the probability of collapse of structures in fire.•The novelty of the methodology lies in adopting the limit analysis with Monte Carlo simulations.•Monte Carlo simulations allow generating a large number of fire scenarios.•The procedure allows calculating the time-dependent vulnerability curve.•The procedure can be used for rapid fire-risk analysis.